As milícias d'El Rey : tropas militares e poder no Ceará setecentista - Gomes, José Eudes Arrais Barroso (2009)
This study aims to discuss the close relation between the military service and the local power in the seaborne Portuguese Empire during the Modern Era. Firstly, it tries to analyses the military forces in Portugal and its overseas empire, debating its wide range of variety and social composition. After that, the study focusses on the conquest and colonization of the captaincy of Ceará during the XVIIIth century, pointing the main role that the military organization played on the formation of the local elites.